Regulatory Challenges of Urban Development in The Russian Federation: The Case of Moscow - Elena MAYOROVA; Elena TEMNOVA (Communications of International Proceedings, 2022)
The paper focuses on the regulatory aspect of sustainable development in Russia and presents the results of the research aimed at eliciting major changes in the Russian approach to using natural resources and urban planning influenced by the global tendency.  The subject matter is the changes in the urban ecological condition as a result of changes in the legislation on urban planning. The objective is to analyse the state of modern environmental legislation, to identify its current trends and controversial provisions and to propose the technique to identify the specific features of legislature in sustainable development in order to show the hazards and potential risks of the subsequent use of natural resources based on the newly shaped regulatory paradigm.  The methods applied are a comprehensive analysis and classification of statistical data, legal definitions on sustainable development in the recent decades, with the applicable use of theoretical modelling and sampling. The sample included acts, enactments and federal legal issues on sustainable development that identify the quality and shift from the ecological paradigm toward the mercenary and acquisitive use of natural resources. The findings of this research have shown challenges of implementing the recent enactments within the newly shaped regulatory paradigm.
Keywords: sustainable development; urban area; comfortable urban environment; green economy; eco-efficiency; environmental legislation; exploitation of natural resources; gentrification.